Social-ecological considerations informing a universal screening strategy for sleep health in the community - Blunden, Sarah; McKellin, William; Herdin, Thomas; Ipsiroglu, Osman S. (Frontiers in Psychiatry, 2023)
‘Poor sleep health’ (PSH), defined as reduced amount of sleep and non-restorative sleep, affects cognitive, social and emotional development. Evidence suggests an association of sleep deprivation and mental health problems; however, there are no universal concepts allowing a first-tier screening of PSH at a community level. The focus of this narrative review is to highlight the cultural context of the current medicalized approach to PSH and to suggest social ecological strategies informing new and holistic community-based screening concepts. We present two conceptual screening frameworks; a ‘medical’ and a merged ‘social emotional wellbeing framework’ and combine them utilising the concept of ‘ecologies’. The first framework proposes the incorporation of ‘sleep’ in the interpretation of ‘vigilance’ and ‘inappropriate’ labelled behaviours. In the first framework we provide a logic model for screening the myriad of presentations and possible root causes of sleep disturbances as a tool to assess daytime behaviours in context with PSH. In the second framework we provide evidence that informs screening for ‘social emotional wellbeing’ in the context of predictive factors, perpetuating factors and predispositions through different cultural perspectives. The distinct goals of both frameworks are to overcome training-biased unidirectional thinking and a priori medicalization of challenging, disruptive and/or disobedient behaviours. The latter has been explicitly informed by the critical discourse on colonisation and its consequences, spearheaded by First Nations. Our ‘transcultural, transdisciplinary and transdiagnostic screening framework’ may serve as a starting point from which adaptations of medical models could be developed to suit the purposes of holistic screening, diagnosis and treatment of complex childhood presentations in different cultural contexts.